The Relationship Between Postpartum Mothers' Knowledge About Jaundice and the Incidence of Neonatal Jaundice in Mrs. T’s Midwifery Practice, Karangtengah District, Cianjur Regency, Indonesia - Suci Saftari Apriani; Tri Handayani; Winda R Anisa (Knowledge Dynamics, 2025)
Background: Neonatal jaundice is a condition that appears on the second and third days of life without any pathological cause, resulting from the rapid breakdown of red blood cells, while some newborns' organs are not yet fully functional in processing bilirubin. After a few days, the liver matures, allowing the bilirubin elimination process to proceed effectively. This research aims to explore the correlation between postpartum mothers' understanding of jaundice and the prevalence of neonatal jaundice at Mrs. T Midwife’s Practic in the Karangtengah District of Cianjur Regency in 2024. Methods: The methodology employed in this research is a quantitative approach utilizing analytical survey methods with a cross-sectional design. The total sample for this study consists of 30 individuals, selected through total sampling. The research tools implemented include questionnaire forms and observation sheets that were validated for reliability, as developed by researcher Dina Yuliarti in 2020. The analysis conducted was both univariate and bivariate. Results: Study findings revealing that a significant number of respondents, totaling 19 people (63.3%), possessed adequate knowledge regarding jaundice, while the majority of respondents who had babies without jaundice numbered 20 (66.7%). Among the mothers with sufficient knowledge, 15 individuals (78.9%) had babies who did not exhibit jaundice. Conclusion: A significant relationship was found between maternal knowledge of jaundice and the occurrence of jaundice in newborns, with a p-value of 0.034, which is less than 0.05.